Implementing COCOMO II as personnel direct cost in an owner estimate cost model for software project. (29th November 2022) - Sholiq, Sholiq; Subriadi, Apol Pribadi; Darmaningrat, Eko Wahyu Tyas; Azis, Abdul
COCOMO II is a method to get effort, time (schedule), and cost for software development. In this study, COCOMO II was used to obtain personnel direct costs of a software development project. Personnel direct costs were one of the three components that compose the owner estimate cost. The purpose of this study was to propose a conceptual model to determine the owner estimate cost that was formed from three components, namely: personnel direct cost, non-personnel direct costs, and taxes. In this study, it was explained the stages of using the model to determine the owner estimate cost for software development projects.